The Effect of Different Octane Number on Power and Specific Fuel Consumption in Gasoline Compression Ignition Engine - Mohammad Adam Fernanda; Bambang Irawan (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
Internal combustion motors are a type of engine used as the main source of power for transportation equipment. This engine functions to convert heat energy into kinetic or motion energy. Compression ignition (CI) utilizes the increase in temperature and pressure during compression to ignite the fuel. The octane number or research octane number (RON) indicates the maximum pressure that can be received before gasoline burns itself. A lower octane number increases the likelihood of detonation of the fuel. Gasoline with a higher octane number is basically designed to prevent premature ignition or auto ignition of the gasoline in the engine. This research focuses on the power and specific fuel consumption of gasoline compression ignition engine at each variation in fuel octane number and engine speed. The fuel used is a mixture of 94% gasoline and 6% diesel fuel. The highest average power results at an engine speed of 1900rpm from 90, 92 and 95 octane fuel respectively are 0.475 kW, 0.728 kW and 0.764 kW. The average results of specific fuel consumption at 1900 engine revolutions were obtained for fuel with octane numbers of 90, 92, and 95 respectively at 0.92 L/kWh, 0.91 L/kWh, and 0.65 L/kWh.